PENGARUH KOMPETENSI KERJA, BEBAN KERJA, DAN SEMANGAT KERJA TERHADAP KEPUASAN KERJA PERAWAT PADA RUMAH SAKIT UMUM PROKLAMASI KARAWANG - Jajang Suhermana; Dedeh Mulyanah (JURNAL BISNIS dan TEKNOLOGI, 2022)
Basically, every employee who works as a nurse at the Proklamasi General Hospital in Karawang has characteristics or has a character based on the abilities that must be mastered. The lack of employee work competence can lead to thoughts of leaving their jobs. In assessing the work carried out at the Karawang Proklamasi General Hospital, employees often receive a warning from the human resource development (HRD) side, which has a negative effect on their performance. This study aims to determine the effect of work competence, workload and morale on the job satisfaction of nurses at the Proklamasi General Hospital in Karawang, either partially or simultaneously. The theory used in this research is Kasmir (2019) about workload, Sutrisno (2017) and Afandi (2018) about job satisfaction, Sugiyono (2019) about quantitative research methods and other sources, both journals and the internet. This type of research uses quantitative research. The population in this study were General Hospital Nurses. In analyzing the data using multiple linear regression, test T, test F and test the coefficient of determination. The results of this study concluded that the variables of work competence, workload, and work spirit were through a partial significant test (T test), which showed that there was a positive and significant effect on the job satisfaction of general hospital nurses. Furthermore, the results of the simultaneous significant test (F test) showed that work competence, workload and work morale simultaneously, had a positive and significant effect on job satisfaction of hospital nurses. The results of this study imply that the factors of work competence, workload, and work spirit are things that need to be considered to increase nurse job satisfaction so that it is even better for the realization of hospital goals.